The Knowledge and Practice in the Self-Medication Use of Topical Benzoyl Peroxide and Clindamycin - Anjarwati, Riska Auliah; Hariadini, Ayuk Lawuningtyas; Ebtavanny, Tamara Gusti (Pharmaceutical Journal of Indonesia, 2025)
Acne vulgaris or acne is a condition of chronic inflammation of the pilosebaceous unit. Topical clindamycin and topical benzoyl peroxide (BP) are therapy with antibacterial and anti-inflammatory effects. The pharmacist's role during self-medication services and the knowledge possessed by the patient are needed to produce the correct drug use. This study aimed to determine the relationship between knowledge and accuracy of using topical benzoyl peroxide and clindamycin self-medication either alone or in combination with students of Brawijaya University with Acne vulgaris. This research was conducted online which is observational analytic with a cross-sectional design. The sampling technique used was a purposive sampling technique based on inclusion and exclusion criteria and 105 respondents were obtained. Student knowledge was measured using a Guttman scale questionnaire with right and wrong answer choices. The accuracy of student use was measured using semi-open questions with multiple-choice answers and essays. The results showed that the respondents had good knowledge (79.05%), sufficient (20.95%), and less (0.00%). Meanwhile, the results of the accuracy of the use of therapy showed that students were correct (60.00%) and not correct (40.00%). The results of the Spearman correlation test showed a significant positive relationship between knowledge and the accuracy of using self-medicated topical benzoyl peroxide and clindamycin therapy (p = 0.012; r = 0.245). Based on the study results, it is concluded that there is a significant positive relationship between knowledge and the accuracy of using self-medicated topical benzoyl peroxide and clindamycin therapy in Brawijaya University students with Acne vulgaris. Keyword: Acne vulgaris, knowledge, practice, benzoyl peroxide, clindamycin